PREPL, a Prolyl Endopeptidase-Like Enzyme by Name Only? Lessons from Patients - Boonen, Kurt; Regal, Luc; Jaeken, Jaak; W.M. Creemers, John (CNS & Neurological Disorders - Drug Targets, 2011)
Deletion of the Prolyl Endopeptidase-like (PREPL) gene has been described in three contiguous gene deletion syndromes at the 2p21 locus and current developments in high resolution microarrays and whole genome sequencing will no doubt soon result in the identification of isolated PREPL deficiency. But by comparing the differences in phenotypes with the number of genes deleted, the contribution of PREPL deficiency can already be deduced. Homozygous or compound heterozygous loss of PREPL is predicted to cause neonatal hypotonia and severe feeding problems. Failure to thrive usually persists for several years, followed by a period of hyperphagia and excessive weight gain. Growth retardation is usually observed, which responds well to growth hormone therapy. In addition, minor facial dysmorphism, nasal speech, viscous saliva, hypergonadotropic hypogonadism and learning problems are frequently observed. How PREPL deficiency causes these clinical manifestations remains unknown. PREPL is highly expressed in brain and based on gene coexpression network architecture it has been placed in a group enriched with markers of neurons and synaptic proteins. PREPL is predicted to be a serine oligopeptidase based on its homology with prolyl endopeptidase (PREP) and the presence of an active catalytic triad. However, until now no substrates have been found. Recent observations that PREP has non-catalytic functions in the cytoplasm through interactions with its amino- terminal propeller domain, suggests that of PREPL may also have biological functions independent of its predicted peptidase activity. This raises the possibility that PREP and PREPL are homologous, not just by name but also by nature.
Keywords: Atypical Hypotonia-Cystinuria Syndrome